Wedo 2.0 and Lego Education for the Logical Development of Elementary School Children - López-Araujo, Marco (2024)
In order to address the limited interest of children in the area of mathematical logic, this article presents strategies aimed at enhancing the logical thinking of elementary school students. To achieve this goal, innovative educational tools were employed, specifically, Wedo 2.0 and Lego Education, which combine Lego figures with block-based programming. The motivation behind this approach is rooted in the ability of Lego objects to captivate students’ attention due to their versatility in terms of colors, shapes, and sizes. By combining these figures with block-based programming, an interactive and stimulating learning environment is created that fosters creativity and the development of logical and mathematical skills. The research methodology used was quantitative and descriptive, and the target population consisted of fourth-grade students at the Oswaldo Guayasamín Educational Unit in Ecuador. The students were divided into two parallel groups, totaling 42 participants. The results of this study revealed a positive impact on the development of students’ logical thinking. The experimental group experienced a significant increase in their average scores, moving from an initial level ranging from low to medium to a medium-high level, with an average score of 6.66. In conclusion, the implementation of educational strategies that combine Wedo 2.0 and Lego Education proved to be effective in improving the logical thinking and mathematical skills of elementary school students.